(untitled) (Zaporizhzhia Historical Review, 2021)
The article touches upon the position of the German school in the years of the World War I in the south of Ukraine. It states that the government of Tzarist Russia struggled against Germans living in the country. The Government tried to accomplish its goals by closing German schools and implementing the politics of russification. Such actions had a very negative impact on German ethnic group.